In Congress, October 17, 1777 : Resolved, that the premium of five dollars, offered by a resolution of Congress of the 31st of July last, for apprehending and securing deserters from the Continental Army, an addition be made of five dollars for each deserter so apprehended and secured . (LLMC-digital (Series), 1777)
October 17, 1777 broadside issued by the Continental Congress, setting a bounty for the return of any deserters.